Disruption of attention to novel events after frontal lobe injury in humans. Issue 1 (1st January 2000) - Daffner, Kirk R; Mesulam, M Marsel; Holcomb, Philip J; Calvo, Vivian; Acar, Diler; Chabrerie, Alexandra; Kikinis, Ron; Jolesz, Ferenc A; Rentz, Dorene M; Scinto, Leonard F M
Abstract : OBJECTIVE: To investigate whether frontal lobe damage in humans disrupts the natural tendency to preferentially attend to novel visual events in the environment. METHODS: Nine patients with chronic infarctions in the dorsolateral prefrontal cortex (DLPFC) and 23 matched normal controls participated in a study in which subjects viewed repetitive background stimuli, infrequent target stimuli, and novel visual stimuli (for example, fragmented or "impossible" objects). Subjects controlled viewing duration by a button press that led to the onset of the next stimulus. They also responded to targets by pressing a foot pedal. The amount of time spent looking at the different kinds of stimuli, and the target detection accuracy and speed served as dependent variables. RESULTS: Overall, normal controls spent significantly more time than frontal lobe patients looking at novel stimuli. Analysis of responses across blocks showed that initially frontal lobe patients behaved like normal controls by directing more attention to novel than background stimuli. However, they quickly began to distribute their viewing time evenly between novel and background stimuli, a pattern that was strikingly different from normal controls. By contrast, there were no differences between frontal lobe patients and normal controls for viewing duration devoted to background and target stimuli, target detection accuracy, or reaction time to targets. Frontal lobe patients did not differ from normal controls in terms of age, education, estimated IQ, or mood, but were more apathetic as measured by self report and informants' judgments. Attenuated responses to novel stimuli significantly correlated with degree of apathy. CONCLUSIONS: This study demonstrates that DLPFC injury selectively impairs the natural tendency to seek stimulation from novel and unusual stimuli. These data provide the first quantitative behavioural demonstration that the human frontal lobes play a critical part in directing and sustaining attention to novel events. The impairment of novelty seeking behaviour may contribute to the characteristic apathy found in patients with frontal lobe injury.